Analysis of Factors Affecting Parents' Purchase Intention on Eco-Friendly Baby Clothing Products in Indonesia - Komara, Catherine Nur; Yuliati, Elevita (International Journal Labs, 2023)
Infants and children need a large quantity of clothing in various sizes during their first two years of life. Therefore, Indonesian parents need to alter their purchasing preferences and buy more eco-friendly baby clothing products. This study aims to develop a thorough framework for analyzing consumer intentions to buy eco-friendly baby clothes. The theoretical base integrates the Theory of Planned Behavior with five additional constructs, including environmental apparel knowledge, social status, green self-concept, environmental concern, and greenwashing concern and two additional moderating variables for perceived aesthetic risk and perceived economic risk An online survey was conducted of 216 married women belonging to the late Y and early Z generations. PLS-SEM was used to determine the structural and measurement model. Based on the study it was found that attitude, subjective norms, and perceived behavioral control have a positive influence on purchase intention. In addition, environmental apparel knowledge and environmental concern have a positive effect on attitude; green self-concept and social status have a positive effect on subjective norms; environmental apparel knowledge and social status have a positive effect on perceived behavioral control. Meanwhile, attitude mediates environmental concerns, subjective norms mediate social status, and perceived behavioral control mediates environmental apparel knowledge and social status. Perceived economic risk moderates the relationship between subjective norms and purchase intention. This study will add to the body of knowledge regarding the design of marketing strategies for clothing products in Indonesia and other developing nations while taking environmental considerations into account.